Proceedings of the 16th International Conference on Human-Computer Interaction With Mobile Devices &Amp; Services 2014
DOI: 10.1145/2628363.2628364
|View full text |Cite
|
Sign up to set email alerts
|

An in-situ study of mobile phone notifications

Abstract: Notifications on mobile phones alert users about new messages, emails, social network updates, and other events. However, little is understood about the nature and effect of such notifications on the daily lives of mobile users. We report from a one-week, in-situ study involving 15 mobile phones users, where we collected real-world notifications through a smartphone logging application alongside subjective perceptions of those notifications through an online diary. We found that our participants had to deal wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
185
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(207 citation statements)
references
References 32 publications
18
185
3
1
Order By: Relevance
“…The fact that only professional services staff restricted their email to personal accounts on their phones suggests that smartphones are considered differently between the two professional groups. In addition, confirming our finding that smartphones intrude even in the most private of moments, Pielot et al [26] found that the number of emails received on smartphones is correlated with stress from receiving work emails after work. Moreover, we are able to confirm that Matthews et al's [20] findings are still valid after five years where people generally still use their phones to triage their email, and computers respond to messages, despite the fact that mobile behaviours are said to have changed over the course of that time [9].…”
Section: Profession Influences Email and Work-home Boundary Managementsupporting
confidence: 90%
“…The fact that only professional services staff restricted their email to personal accounts on their phones suggests that smartphones are considered differently between the two professional groups. In addition, confirming our finding that smartphones intrude even in the most private of moments, Pielot et al [26] found that the number of emails received on smartphones is correlated with stress from receiving work emails after work. Moreover, we are able to confirm that Matthews et al's [20] findings are still valid after five years where people generally still use their phones to triage their email, and computers respond to messages, despite the fact that mobile behaviours are said to have changed over the course of that time [9].…”
Section: Profession Influences Email and Work-home Boundary Managementsupporting
confidence: 90%
“…However, as seen from Figure 4, some users receive as many as 200 notifications on some days and only a few on other days. This trend corresponds in size and distribution to those push notifications collected by Pielot et al [15] and also those observed …”
Section: Datasetssupporting
confidence: 87%
“…These messages have become so popular that users now receive hundreds of push notifications per day, many of which are non critical and does not require immediate attention (excluding SMS, and messages from other real time communication services, e.g., Skype, WhatsApp, etc.) [13,15]. While the impact of this increase has been studied in terms of its disruptive aspects on the end users, little attention has been given to the push notification delivery services from a system perspective and their impact on energy consumption on the mobile device.…”
Section: Introductionmentioning
confidence: 99%
“…With mobile devices, researchers are able to collect large quantities of data over broad geographical areas. Further, the use of smartphone-based applications ('apps') provides access to functionality such as location-based activity detection [13,14] and notifications [15] that can help improve survey compliance and data completeness of survey responses. These features can help overcome known limitations of paper surveys, such as recall bias and transcription error, to improve overall reliability of results [16].…”
Section: Patient Experience Surveysmentioning
confidence: 99%